2007
DOI: 10.1080/09639280701430306
|View full text |Cite
|
Sign up to set email alerts
|

Concept Mapping in a Financial Accounting Theory Course

Abstract: This paper assesses the usefulness of concept mapping (an educational learning, assessment, and curriculum development technique developed by Novak, widely used in the natural sciences) within an accounting education context. It shows how an accounting-based concept map can be constructed by students and educators to provide a visual, conceptually transparent graphical representation of an individual's understanding of a particular knowledge domain. The method is firmly routed in Ausubel's theory of meaningful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
1
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 44 publications
0
34
1
3
Order By: Relevance
“…Since its inception as a formal technique, concept mapping has been widely used in academic disciplines, for example, Accounting (Chei-Chang 2008; Irvine et al 2005;Leauby and Brazina 1998;Maas and Leauby 2005;Simon 2007;van der Laan and Dean 2006), Finance (Biktimirov and Nilson 2003), Engineering (Walker and King 2002), Statistics (Schau and Mattern 1997), Reading Comprehension (Mealy and Nist 1989), Biology (Kinchin 2000), Nursing (Baugh and Mellott 1998;King and Shell 2002;Schuster 2000;Wilkes et al 1999), Medicine (Hoffman et al 2002;McGaghie et al 2000;West et al 2000), Nursing (Beitz 1998) and Veterinary Science (Edmonson 1993).…”
Section: Concept Mappingmentioning
confidence: 99%
“…Since its inception as a formal technique, concept mapping has been widely used in academic disciplines, for example, Accounting (Chei-Chang 2008; Irvine et al 2005;Leauby and Brazina 1998;Maas and Leauby 2005;Simon 2007;van der Laan and Dean 2006), Finance (Biktimirov and Nilson 2003), Engineering (Walker and King 2002), Statistics (Schau and Mattern 1997), Reading Comprehension (Mealy and Nist 1989), Biology (Kinchin 2000), Nursing (Baugh and Mellott 1998;King and Shell 2002;Schuster 2000;Wilkes et al 1999), Medicine (Hoffman et al 2002;McGaghie et al 2000;West et al 2000), Nursing (Beitz 1998) and Veterinary Science (Edmonson 1993).…”
Section: Concept Mappingmentioning
confidence: 99%
“…The results of Okoye and Okechukwu (2010) showed that the concept-mapping strategy is more effective in enhancing students' achievement in biology than the lecture method. However, there was no significant main effect of gender on the treatment., other supporting studies were of Simon (2007), Ezeudu (2013), Abdulkarim and Hassan (2013) which revealed that there was no gender influence on students' concept-mapping ability and their achievement in the subject.…”
Section: Review Of Related Literaturementioning
confidence: 99%
“…Argument mapping can be integrated where ''concept'' or ''mind'' mapping techniques are already being used in subjects such as Accounting and Finance (Biktimirov and Nilson 2006;Simon 2007;van der Laan and Dean 2007). Work is being done on ways of integrating concept mapping and argument mapping.…”
Section: Discussionmentioning
confidence: 99%